Analisis Kemampuan VO2MAX Pemain yang Bermain pada Posisi Center Midfielder - Muhammad Anas Fawwaz Muharram; Habil Muhbaedillah; Berliana (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
The purpose of this study was to determine the VO2max levels of SSB Java One Top U-15 players and PS Java Top senior players who play in the center midfielder position. The method of this study was quantitative research with a descriptive approach. Data collection was conducted through a VO2max test using the Yo-Yo Intermittent Recovery Test Level 1 (YYIR1). The research subjects consisted of 11 SSB Java One Top U-15 players and 7 PS Java Top senior players who played in the center midfielder position. The results showed that among the 11 SSB Java One Top U-15 players, none were classified in the high VO2max category, 5 players were in the moderate category, and 6 players were in the low category. Meanwhile, among the 7 PS Java Top senior players, 1 player was classified in the high VO2max category, 3 players were in the moderate category, and the remaining 3 players were in the low category. In conclusion, the aerobic endurance ability of players in the center midfielder position still needs to be developed and improved through training programs that are adjusted to match demands. Keywords: Endurance, Center Midfielder, Physical Condition, Football, VO2MAX